Golgi: Interactive Online Brain Mapping - Brown, Ramsay A.; Swanson, Larry W. (Frontiers in Neuroinformatics, 2015)
Golgi (http://www.usegolgi.com) is a prototype interactive brain map of the rat brain that helps researchers intuitively interact with neuroanatomy, connectomics, and cellular and chemical architecture. The flood of '-omic' data urges new ways to help researchers connect discrete findings to the larger context of the nervous system. Here we explore Golgi's underlying reasoning and techniques and how our design decisions balance the constraints of building both a scientifically useful and usable tool. We demonstrate how Golgi can enhance connectomic literature searches with a case study investigating a thalamocortical circuit involving the Nucleus Accumbens and we explore Golgi's potential and future directions for growth in systems neuroscience and connectomics.